Forced convection mass deposition and heat transfer onto a cylinder sheathed by protective garments. Issue 1 (21st October 2013) - Ambesi, Davide; Kleijn, Chris R.; den, Emiel A.; Bouma, Richard H. B.; Brasser, Paul
<x xml:space="preserve">Abstract</x> In chemical, biological, radiological, and nuclear protective clothing, a layer of activated carbon material in between two textile layers provides protection against hazardous gases. A cylinder in cross flow, sheathed by such material, is generally used to experimentally test the garment properties. This is, however, complicated and predictive models are needed. We present a computational fluid dynamics model for the initial phase in which the carbon filter material is not yet saturated. The textiles are modeled as chemically inactive porous layers, the carbon filter particles have been resolved explicitly. The model has been validated against experimental data. We demonstrate that (1) computational fluid dynamics simulations can be used for the efficient design and optimization of protective garments, and (2) the addition of a highly porous active carbon layer highly increases the chemical protection capabilities, while having relatively little negative impact on the thermal comfort of protective garments. © 2013 American Institute of Chemical Engineers AIChE J, 60: 353–361, 2014